Penerapan Model Dua Tinggal Dua Tamu dalam Upaya Meningkatkan Motivasi dan Hasil Belajar Peserta Didik Kelas I SD Negeri 47 Mataram - Fatimah, Fatimah (Jurnal Paedagogy, 2019)
This study aims to determine the effectiveness of the TT Duo An Competitive Prize model in an effort to increase motivation and learning outcomes of Class I students of SD Negeri 47 Mataram. The benefits of this research are encouraging students to develop learning skills in groups (cognitive) and to socialize with friends as a learning process in the classroom. And for teachers to improve the development of approaches and models of learning by applying scientific and discovery learning strategies in group work learning (cooperative) with the discussion method. This research was conducted in two cycles, each cycle of activities is; planning, implementation, observation and reflection. The final results of the action in the second cycle showed that the teacher’s observation of 4.50, the results of student observations reached an average score (4.21). While the acquisition of student learning outcomes reaches an average value (87.31), meaning that indicators of success (> 4.0) and learning outcomes (> 75.00) have been exceeded. Because the indicators of success have been achieved, the study was declared successful and stopped in cycle II.